The multi-faceted nature of freedom in the life and works of Czesław Miłosz - Głuszak, Michał (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The article discusses the issue of freedom in the work of Czesław Milosz. This problem is analyzed in relation to prose, poetry, essay writing, journalism, as well as numerous interviews that Milosz gave throughout his whole life. The author of the article is particularly interested in Milosz’s attitude to the sexual revolution of 1968, which he observed as a professor at Berkley. The poet was not an indifferent witness to this event. He often referred to it, often returned to it, as the author shows, not without ambivalence.